Journey of the universe - Northcutt, Patsy; Kennard, David; Swimme, Brian; Tucker, Mary Evelyn; Northcutt Productions; Soundview Media Partners ([Mill Valley, Calif.] : Northcutt Productions, 2011)
Journey of the universe guides us through an elegant telling of the ways in which galaxies and stars, planets and living organisms emerged within the vast drama of the universe, from the origins of life to our present challenges. Today the survival of species and entire ecosystems depends upon the choices humans make.
Originally released as a motion picture in 2011.
Host, Brian Thomas Swimme.
Cinematographer, Ian Salvage ; editor, Patsy Northcutt ; music, Christopher Ward.
In English with optional Spanish subtitles.
Winner of an Award at Northern California Emmy Awards 2012 : Best Documentary
Online resource; title from opening/closing credits (Digitalia Film Library, viewed May 5, 2017).
Keywords: Cosmology -- Popular works; Astronomy -- Popular works; Evolution -- Popular works; Nonfiction films; Documentary films; Internet videos; Streaming video